Advanced Biological Therapies: Principles, Mechanisms and Medical Applications - Rafal Brozek; Antonina Lorenz; Barbara Dorocka-Bobkowska; Maciej Kurpisz (Journal of Clinical Medicine, 2026)
Biotherapeutics are medicinal agents derived from or related to naturally occurring molecules in the body and are designed to modulate specific immune targets. This review examines clinically established biologics and targeted small molecules that affect cytokine-driven transcriptional programs, principally JAK/STAT and canonical and non-canonical NF-κB signaling, across autoimmune, neoplastic, hematological, dermatological, and rheumatic diseases. Periodontitis is used as a translational model because dysbiotic mucosal inflammation, cytokine signaling, and osteoclastogenesis may also intersect with systemic autoimmunity. In particular, Porphyromonas gingivalis-associated protein citrullination provides a plausible link to anti-citrullinated protein antibody-positive rheumatoid arthritis in genetically susceptible individuals, although causality remains unproven. The review also evaluates plant-derived modulators of JAK/STAT and related transcriptional pathways. Curcumin and resveratrol have entered small rheumatoid arthritis studies, whereas evidence for catechins, celastrol, and artemisinin derivatives in autoimmune disease remains predominantly preclinical. These compounds may inform adjunctive or locally delivered strategies, but clinical translation requires better target selectivity, bioavailability, dose standardization, and safety data.